Anxiety, Depression, Loneliness, Spirituality, and Social Support in Older People During the COVID-19 Pandemic - Esti Widiani; Nurul Hidayah; Abdul Hanan (Jurnal Keperawatan Indonesia, 2023)
The COVID-19 pandemic has resulted in the threat of death. Some older people feel they are not ready to face the end of their lives, so psychosocial problems arise, such as loneliness, anxiety, and depression. This research study aims to explore some psychosocial aspects, namely spirituality, social support, depression, anxiety, and loneliness in the elderly during the pandemic. The research design was cross-sectional. The total sample was 142 people selected using the purposive sampling method. Data collection used various scales to look at spirituality, depression, anxiety, and loneliness. The results showed that median spirituality and social support scores were high. The median depression and loneliness scores were mild. The average anxiety score for the elderly was normal. Based on the Pearson and Spearman correlation tests, relationships were shown between spirituality and anxiety scores, social support and anxiety scores, anxiety and depression scores, and loneliness and depression scores. The elderly need spirituality and social support when facing the end of life, and during the COVID-19 pandemic, to prevent the emergence of psychosocial problems. Social support and high spirituality must be maintained, even though the pandemic has subsided, in case such a health crisis occurs again.   Abstrak Kecemasan, Depresi, Kesepian, Spiritualitas, dan Dukungan Sosial pada Lansia Saat Pandemi COVID-19. Pandemi COVID-19 mengancam banyak jiwa. Sebagian dari lansia merasa belum siap menghadapi akhir kehidupan seperti kematian sehingga muncul masalah psikososial seperti kesepian, cemas, dan depresi. Penelitian ini bertujuan untuk mengetahui aspek psikososial lansia yaitu spiritualitas, dukungan sosial, depresi, kecemasan, dan kesepian selama pandemi COVID-19. Desain penelitian yang digunakan adalah cross-sectional. Jumlah sampel sebanyak 142 orang yang dipilih dengan metode purposive sampling. Pengumpulan data menggunakan berbagai kuisioner untuk melihat spiritualitas, depresi, kecemasan, dan kesepian. Hasil penelitian menunjukkan bahwa median skor spiritualitas dan dukungan sosial termasuk tinggi. Nilai median depresi dan kesepian tergolong ringan. Rata-rata skor kecemasan lansia adalah normal. Berdasarkan uji korelasi Pearson dan Spearman, ditunjukkan hubungan antara skor spiritualitas dan kecemasan, skor dukungan sosial dan kecemasan, skor kecemasan dan depresi, serta skor kesepian dan depresi. Lansia membutuhkan spiritualitas dan dukungan sosial dalam menghadapi akhir kehidupan maupun saat pandemi COVID-19 untuk mencegah munculnya masalah psikososial. Dukungan sosial dan spiritualitas yang tinggi harus tetap dijaga, walaupun pandemi COVID-19 sudah mereda, agar mampu bertahan jika krisis kesehatan muncul kembali. Kata Kunci: depresi, dukungan sosial, kecemasan, kesepian, spiritualitas